2017
DOI: 10.5047/absm.2017.01003.0041
|View full text |Cite
|
Sign up to set email alerts
|

Toxins of Pufferfish—Distribution, Accumulation Mechanism, and Physiologic Functions

Abstract: Keywordsunit) is defined as the amount of toxin required to kill a 20-g male mouse within 30 min after intraperitoneal administration], and the minimum lethal dose (MLD) for humans is estimated to be approximately 10000 MU (ª2 mg) (Noguchi and Ebesu 2001).The main symptoms of human intoxication include numbness of lips, tongue and the limbs, paresthesia, dysarthria, respiratory distress, and death is caused by respiratory failure in the most critical cases (Noguchi and Ebesu 2001). According to Toda et al. (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…Their extracts were analyzed by LC-MS/MS and were found to contain the parent TTX, at levels of 93 ng and 88 ng TTX per liter of culture, respectively [52]. Certain works supporting an entirely endogenous origin of TTX even support that, in the case of some pufferfish species, where TTX plays a defense mechanism role, extant bacteria are not involved anymore in TTX biosynthesis, despite the initial bacterial origin of their biosynthetic genes [56]. Notably though, TTX is not present in exclusively freshwater-living fauna, not returning to aqueous systems for breeding reasons [57], which may also point to an association of TTX production with marine bacteria.…”
Section: Origin and Sources Of Ttxmentioning
confidence: 99%
See 1 more Smart Citation
“…Their extracts were analyzed by LC-MS/MS and were found to contain the parent TTX, at levels of 93 ng and 88 ng TTX per liter of culture, respectively [52]. Certain works supporting an entirely endogenous origin of TTX even support that, in the case of some pufferfish species, where TTX plays a defense mechanism role, extant bacteria are not involved anymore in TTX biosynthesis, despite the initial bacterial origin of their biosynthetic genes [56]. Notably though, TTX is not present in exclusively freshwater-living fauna, not returning to aqueous systems for breeding reasons [57], which may also point to an association of TTX production with marine bacteria.…”
Section: Origin and Sources Of Ttxmentioning
confidence: 99%
“…Nevertheless, some scientific evidence strongly indicate the exogenous toxification of aquatic organisms as a valid theory [56], that is: (1) the remarkable individual and regional variations in pufferfish toxicity, (2) TTX accumulation by the trumpet shell Charonia sauliae through ingestion of toxic starfish, and (3) TTX absence in artificially cultured pufferfish Takifugu rubripes and T. niphobles when fed non-toxic diets, in contrast to their ability for efficient accumulation following oral TTX administration. In this context, it is suggested that aquatic organisms, such as pufferfish, do not synthesize TTX, but acquire it instead from other toxic organisms bearing bioconcentrated TTX through the food chain with marine bacteria being at the start [58].…”
Section: Origin and Sources Of Ttxmentioning
confidence: 99%
“…Tetrodotoxin (TTX), a potent neurotoxin, is the main toxin component of marine pufferfish of the genus Takifugu, including Takifugu rubripes and Takifugu pardalis, which inhabit the coastal waters of Japan [1][2][3]. Organs such as the liver, ovary, and, in some species, the skin, are generally highly toxic, while the muscle and testes are nontoxic or only weakly toxic [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that TTX may be initially synthesized by marine bacteria and transferred to pufferfish via the food chain [2,18]. Nevertheless, the mechanisms of TTX accumulation in the pufferfish through a toxic food chain, and its elimination remains to be elucidated [19].…”
Section: Introductionmentioning
confidence: 99%